2013
DOI: 10.1029/2011wr011533
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying uncertainty sources in an ensemble of hydrological climate‐impact projections

Abstract: [1] The quantification of uncertainties in projections of climate impacts on river streamflow is highly important for climate adaptation purposes. In this study, we present a methodology to separate uncertainties arising from the climate model (CM), the statistical postprocessing (PP) scheme, and the hydrological model (HM). We analyzed ensemble projections of hydrological changes in the Alpine Rhine (Eastern Switzerland) for the near-term and farterm scenario periods 2024-2050 and 2073-2099 with respect to 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
310
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 339 publications
(328 citation statements)
references
References 68 publications
18
310
0
Order By: Relevance
“…Major uncertainties associated with estimating future floods are related to the effects and interactions of the following components in the model chain (e.g., Bosshard et al, 2013): (1) climate model projections; (2) downscaling/bias correction techniques; and (3) hydrological model uncertainties in the region studied.…”
Section: Methodological Uncertaintiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Major uncertainties associated with estimating future floods are related to the effects and interactions of the following components in the model chain (e.g., Bosshard et al, 2013): (1) climate model projections; (2) downscaling/bias correction techniques; and (3) hydrological model uncertainties in the region studied.…”
Section: Methodological Uncertaintiesmentioning
confidence: 99%
“…Dankers and Feyen (2008) and Hirabayashi et al (2008) indicated a decrease in water flow, whereas Lehner et al (2006) suggested an increase, and Arheimer et al (2012) projected very little overall change in water discharge to the Baltic Sea. Discrepancies between conclusions regarding the future can arise due to uncertainties in GCMs, downscaling methods, or hydrological models (e.g., Bosshard et al, 2013;Donnelly et al, 2014;Hall et al, 2014).…”
Section: Changes In High Flows In Swedenmentioning
confidence: 99%
“…ANOVA could underestimate variance when the sample size is small (Bosshard et al, 2013). To reduce the effect of the sample size, Bosshard et al (2013) proposed a subsampling method, which was used in this paper.…”
Section: Subsampling Approachmentioning
confidence: 99%
“…To reduce the effect of the sample size, Bosshard et al (2013) proposed a subsampling method, which was used in this paper. In the subsampling method, the superscript j in Eq.…”
Section: Subsampling Approachmentioning
confidence: 99%
See 1 more Smart Citation